Methodology for local climate vulnerability assessment and prioritization of climate change adaptation measures in order to elaborate municipal climate change adaptation plan - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The methodology has been sucessfully applied in 2 municipalities of Honduras.